Acute Right Coronary Ostial Stenosis during Aortic Valve Replacement - Umran, Sarwar (Medknow Publications & Media Pvt Ltd, 2012)
We report a rare case of acute right coronary artery stenosis developing in a patient undergoing aortic valve replacement. We present a case report with a brief overview of the literature relating to coronary artery occlusion associated with cardiac valve surgery – the theories and treatments are discussed. A 85 year-old female was admitted under the care of the cardiothoracic team with signs and symptoms of heart failure. Investigations, including cardiac echocardiography and coronary angiography, indicated a critical aortic valve stenosis. Intraoperative right ventricular failure ensued post aortic valve replacement. Subsequent investigations revealed an acute occlusion of the proximal right coronary artery with resultant absence of distal flow supplying the right ventricle. An immediate right coronary artery bypass procedure was performed with resolution of the right ventricular failure. Subsequent weaning off cardiopulmonary bypass was uneventful and the patient continued to make excellent recovery in the postoperative phase. To our knowledge this is one of the few documented cases of intraoperative acute coronary artery occlusion developing during valve surgery. However, surgeons should be aware of the potential for acute occlusion so that early recognition and rapid intervention can be instituted.